2014
DOI: 10.1083/jcb.2072oia191
|View full text |Cite
|
Sign up to set email alerts
|

microRNA-mediated regulation of mTOR complex components facilitates discrimination between activation and anergy in CD4 T cells

Abstract: T cell receptor (TCR) signals can elicit full activation with acquisition of effector functions or a state of anergy. Here, we ask whether microRNAs affect the interpretation of TCR signaling. We find that Dicer-deficient CD4 T cells fail to correctly discriminate between activating and anergy-inducing stimuli and produce IL-2 in the absence of co-stimulation. Excess IL-2 production by Dicer-deficient CD4 T cells was sufficient to override anergy induction in WT T cells and to restore inducible Foxp3 expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“…Moreover, in our study, mTOR was identified as the direct target of miR-15/16 in CD81 T cells. Our results are in concordance with Antoine Marcais's study 18 in CD4 T cells, Dice deficiency confers increased sensitivity of CD4 T cells to TCR signals and the mTOR components were targeted by the microRNAs Let-7 and miR-16.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Moreover, in our study, mTOR was identified as the direct target of miR-15/16 in CD81 T cells. Our results are in concordance with Antoine Marcais's study 18 in CD4 T cells, Dice deficiency confers increased sensitivity of CD4 T cells to TCR signals and the mTOR components were targeted by the microRNAs Let-7 and miR-16.…”
Section: Discussionsupporting
confidence: 93%
“…[13][14][15] Recent studies showed that miR-15a/16 also acted as an immune regulator in physiological and inflammatory conditions, impacting macrophage phagocytosis, 16 NK maturation 17 and T cell activation. 18 Therefore, we reasoned that targeting miR-15a/16 in the tumor microenvironment may attenuate glioma progression. To test this hypothesis, glioma expansion and survival time was examined in both wild-type (WT) and miR-15a/16 deficient C57BL/6 mice intracranially injected with the syngeneic glioma GL261 cells.…”
Section: Introductionmentioning
confidence: 99%
“…In dendritic cells activated by LPS, let-7 inhibits Socs1 , which promotes dendritic cell maturation and their ability to drive T cell proliferation (Kim and others 2013; Zhang and others 2011). let-7 may also limit self-renewal of memory T cells (Almanza and others 2010), suppress CD4 + T cell activation, promote T cell anergy (Marcais and others 2014), and inhibit T h 17 cell differentiation (Zhang and others 2013). In the CNS, let-7 limits microglial activation (Cho and others 2015) and promotes differentiation of cultured glial progenitor cells into astrocytes (Shenoy and others 2015).…”
Section: Micrornas: Role In Cns Neuroinflammationmentioning
confidence: 99%
“…Prior examination of miR-16 suggests regulation of Beclin dependent autophagy via inhibition of Bcl-2 in carcinomas [Pattingre et al, 2005;Xu et al, 2014;Huang et al, 2015a]. miR-16 has also been implicated in regulating protein synthesis through mTOR inhibition in both immune and cancer cells [Janaki Ramaiah et al, 2014;Marcais et al, 2014]. Janaki Ramaiah et al [2014] demonstrated direct binding of miR-16 to the 3 0 -UTR of the protein synthetic regulator Rps6kb1 (subunit of p70S6K1) and the down-regulatory effects observed at the protein level in multiple cancer cell lines.…”
mentioning
confidence: 99%